Leishmaniasis in rheumatology, haematology and oncology: Epidemiological, immunological and clinical aspects and caveats - Bogdan, Christian (Annals of the Rheumatic Diseases, 2012)
Leishmaniasis is an intracellular protozoan infection that can lead to cutaneous, mucocutaneous, visceral or systemic manifestations depending on the parasite species and virulence and on the host immune response. It is endemic in countries of Europe (Mediterranean basin), Asia, Africa, Central and South America, but autochthonous cases begin to emerge outside classical disease areas. CD4+ T helper cells, interferon γ, dendritic cells and macrophages are the key components of antileishmanial defence. Leishmaniasis is an important differential diagnosis in patients with chronic lesions of the skin or mucous membranes or with fever, hepatosplenomegaly, lymphadenopathy, pancytopenia, histocytosis, haemophagocytic syndrome or glomerulonephritis. Organ transplant recipients and patients with autoimmune syndromes are at particular risk of developing visceral leishmaniasis following immunosuppressive therapy (eg, with steroids, methotrexate, ciclosporin or tumour necrosis factor-neutralising biological agents). Diagnosis and adequate treatment of leishmaniasis requires the combined use of culture, microscopic and nucleic acid amplication methods and species identification by sequencing and other molecular techniques. Standard regimens for the treatment of visceral leishmaniasis are intravenous liposomal amphotericin B (3 mg/kg body weight for 10 days) or oral miltefosine (150 mg/day for 28 days).
CRIS-Team Scopus Importer:2024-02-26